Minor trauma-induced eccrine porocarcinoma of the toe in a patient on long-term carbamazepine: a case report and literature review - Yang, Lianbo; Lv, Jinghang; Zhao, Xinghan; Zheng, Ziang; Cui, Xinyao; Lin, Jiabin; Wang, Yifan; Liang, Haidong (Frontiers in Oncology, 2026)
BackgroundEccrine Porocarcinoma is a rare malignant neoplasm of eccrine sweat gland origin. Its diverse clinical presentation often leads to misdiagnosis and delayed treatment. The potential role of systemic factors, such as long-term medication use, in its pathogenesis is poorly understood.Case presentationWe report a case of a 51-year-old male with a 30-year history of epilepsy on long-term carbamazepine therapy, who developed a refractory ulcerative mass on the left second toe after minor trauma. Toe amputation was performed, and histopathology confirmed Eccrine Porocarcinoma.ConclusionsThis case highlights the importance of considering rare malignancies like Eccrine Porocarcinoma in the differential diagnosis of non-healing acral ulcers. An early biopsy is crucial. The long-term use of carbamazepine in this context is noted, and its potential role as a co-factor in tumor development, possibly interacting with local chronic inflammation, is discussed. Further investigation into the influence of systemic medications on the pathogenesis of such rare tumors is warranted.